DEMOKRATISASI PENDIDIKAN: TINJAUAN TEORETISDAN PANDANGAN ISLAM - Ali Masykur Tanjung; Abdul Sahib; Abu Muslim (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
This research explores the concept of democracy in education from a theoretical perspective and Islamic views. Educational democracy includes active participation of all parties in the educational process, critical development, and respect for diversity. In Islam, education plays a role in forming the character of individuals who have noble character and broad knowledge. This research uses a qualitative method with a descriptive-analytical approach through literature study. The research results show that democracy in education is in harmony with Islamic values ​​which prioritize justice, equality and social responsibility.